Numerical study on permeability of gas diffusion layer with porosity gradient using lattice Boltzmann method. (18th June 2021) - Wang, Hao; Yang, Guogang; Li, Shian; Shen, Qiuwan; Liao, Jiadong; Jiang, Ziheng; Espinoza-Andaluz, Mayken; Su, Fengmin; Pan, Xinxiang
Abstract: In this paper, the lattice Boltzmann method (LBM) has been employed to explore the permeability and internal fluid flow behavior of the gas diffusion layer (GDL). Three different non-uniform porosity distributions are designed as linear type, stepped type, and transitional type and compared with constant porosity samples. Results show that the linear porosity gradient distribution leads to higher permeability values compared with the other two types. For samples with total porosity of 0.65 and 0.75, optimal porosity gradient distributions bring about an enhancement of permeability have been found. The impact of porosity gradient distribution on the velocity field is presented. Dependencies of permeability with porosity and tortuosity are demonstrated through several fitted equations. Highlights: The lattice Boltzmann method is employed to study the permeability of porosity gradient GDL. GDL porosity distributions have strong influence of fluid flow behavior. A little increase of porosity along main flow direction leads to higher permeability. Expressions are fitted to reveal the correlation between permeability and tortuosity.